The biomechanical characteristics of human vestibular aqueduct: a numerical-based model construction and simulation. Issue 8 (11th June 2021) - Guan, Qingjie; Sun, Dong; Zhao, Ming; Liu, Yingxi; Yu, Shen; Zhang, Jianing; Li, Rui; Sun, Kaili; Sun, Xiuzhen; Bie, Xu
Abstract: Vestibular aqueduct is a precise structure embedded in the temporal bone and plays a key role in the physiological function of inner ear by maintaining the endolymphatic circulation and buffering the impact from intracranial pressure. Although the alterations on the morphology or volume of vestibular aqueduct result in variety of diseases, the approaches of evaluating the condition of vestibular aqueduct are still unsatisfing because the pathological sections utilized for the 3D construction model most likely undergoes morphological changes. In this study, the vestibular aqueduct images obtained by CT scanning were processed by finite element method to construct the 3D model. To assess if this numerical model reflects the actual biomechanical properties of vestibular aqueduct, the fluid-solid coupling calculation was applied to simulate the endolymphatic flow in the vestibular aqueduct. By measuring the dynamics of endolymphatic flow, and the pressure and displacement on round membrane under external pressure, we found the numerical 3D model recapitulated the biomechanical characteristics of the real vestibular aqueduct. In summary, our approach of 3D model construction for vestibular aqueduct will provide a powerful method for the research of vestibular aqueduct-related diseases.